TINJAUAN HUKUM TERHADAP ANAK SEBAGAI OBJEK KAJIAN VIKTIMOLOGI DALAM KEJAHATAN PROSTITUSI - Diko Anggalih Utomo dan Fitri Ayu Ranti, Benaya Hendriawan (GEMA, 2015)
The continued development of the times many crimes with various styles or modes of doing evil, whether organized or individual person as the perpetrator. Children are often used as a wide variety of crime victims one crime of prostitution. The problem that arises is when the child does not know if they are victims of crime and do not know how to overcome that evil in prostitution environment and continuous recurrence occurred. Then this journal examines a child as an object of Victimology by positioning children as victims of crime, forms of victimization, effects and influence in society with the aim of providing knowledge to children as victims of crime in the scope of prostitution.Child prostitution or child prostitution is the act of obtaining or offering sexual services of a child by a person or to others in exchange for money or other remuneration. Child prostitution is a form of Commercial Sexual Exploitation of Children (CSEC). Forms of exploitation of other children are like the trafficking of children for sexual purposes and child pornography. Each form is often closely interrelated with each other.Child protection is all activities to ensure and protect children and their rights in order to live, grow, develop, and participate optimally in accordance with human dignity, as well as protection from violence and discrimination. Indonesian legal protection for prostituted children have not been sufficient to ensure the protection by using a standard childrens rights contained in international instruments on the rights of children. Statury rape applied in Indonesia is also considered to be very low, which is under twelve years.